2006
DOI: 10.1152/ajpcell.00008.2006
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1 expression in adipose tissue: effects of diet-induced obesity in mice

Abstract: . ICAM-1 expression in adipose tissue: effects of diet-induced obesity in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 56 publications
8
108
0
Order By: Relevance
“…Previous studies reported that the expression of adhesion molecules in visceral adipose tissue was increased by obesity [36,37]. In another study, obese mice did not exhibit macrophage infiltration into adipose tissue after ICAM-1 antagonist treatment [38].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies reported that the expression of adhesion molecules in visceral adipose tissue was increased by obesity [36,37]. In another study, obese mice did not exhibit macrophage infiltration into adipose tissue after ICAM-1 antagonist treatment [38].…”
Section: Discussionmentioning
confidence: 88%
“…Previous reports showed that the expression of adhesion molecules in adipose tissue was increased in the obese condition [5,6] and a different study indicated that HFD induced obese mice exhibited higher expression of Intercellular adhesion molecule 1(ICAM-1) and Vascular cell adhesion [7]. Thus, adhesion molecules affect obesity-induced macrophage infiltration into adipose tissue.…”
Section: Introduction *mentioning
confidence: 97%
“…Adhesion molecules such as intercellular adhesion molecule (ICAM)-1 have been shown to be expressed in murine AT [33]. Furthermore, it has been shown in mice that within 3 weeks of high-fat feeding, AT expression of ICAM-1 was increased, and after 6 months of feeding, soluble ICAM-1 in plasma correlated with bodyweight and fat mass [34]. Most recently, Nishimura et al used in vivo imaging to show that leukocyte-EC interactions are increased in the microcirculation of the subcutaneous AT of obese mice, and that administration of antibody to ICAM-1 normalized these interactions [35].…”
Section: Endothelial Cell-mediated Adhesionmentioning
confidence: 99%
“…In obese mice and humans, M⌽s infiltrate AT as circulating monocytes in response to AT secretion of MCP-1, which recruits monocytes expressing the C-C chemokine receptor (CCR)2 (1,2,10 -12,13). CCR2ϩ M⌽s expressing the M⌽ differentiation marker F4/80 and CD11c, a dendritic cell (DC) marker (13) upregulated in M⌽ foam cells (14), were recently reported to infiltrate AT of obese mice and were distinguished from noninflammatory resident ATM⌽s (F4/ 80ϩ/CCR2Ϫ/CD11cϪ) isolated from nonobese mice (12,15). However, the relationship between this obesityassociated ATM⌽ "phenotypic switch" (12) and the development and progression of obesity complications is unclear (16,17).…”
mentioning
confidence: 99%